Epistemologies of the South and Africa's Marginalization in the Media - Zvenyika Eckson Mugari (Palgrave Macmillan, Cham, 2022)
This chapter analyzes the relationship between how knowledges produced in the global south are treated and how western media projects the continent. Extant scholarly literature on the news media can be classified into three broad areas focusing on: the nature of media organization, production processes, news texts, and news reception. Research pursuit of these areas is premised mainly on the basic assumption that the news matters. By implication, non-news is an irrelevance for the simple reason that it is an absence and therefore not known and available to the research community. Thus, the western dominant news episteme stayed the course and remained hegemonic and, so has the product of its epistemic processes, the news, enjoyed the status of quintessential truth.